2021
DOI: 10.1097/wno.0000000000001424
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prognostic Model for Predicting Multiple Sclerosis After Optic Neuritis: A Secondary Analysis of Data From the Optic Neuritis Treatment Trial

Abstract: Background:Optic neuritis can be the initial manifestation of multiple sclerosis (MS). The purpose of this study was to develop a prognostic model for predicting the risk of MS development among patients with optic neuritis.Methods:The data from 388 patients with optic neuritis were retrieved from the Optic Neuritis Treatment Trial (ONTT). Cox proportional hazards regression analysis was used to develop a prognostic model. The performance of the model was assessed by using Harrell's C-index and calibration cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the ONTT, high-dose intravenous methylprednisolone may reduce the risk of MS occurrence ( 22 ), and in theory, this decrease may also lower the risk of disability. However, our analysis did not observe such an occurrence, so further research is needed to investigate the actual impact of corticosteroid therapy on disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ONTT, high-dose intravenous methylprednisolone may reduce the risk of MS occurrence ( 22 ), and in theory, this decrease may also lower the risk of disability. However, our analysis did not observe such an occurrence, so further research is needed to investigate the actual impact of corticosteroid therapy on disability.…”
Section: Discussionmentioning
confidence: 99%
“…In our finding, we observed that patients with optic neuritis who had clinically definite MS at baseline had a higher risk of developing disability compared to those who were not diagnosed with MS. In the ONTT, high-dose intravenous methylprednisolone may reduce the risk of MS occurrence (22), and in theory, this decrease may also lower the risk of disability. However, our analysis did not observe such an occurrence, so further research is needed to investigate the actual impact of corticosteroid therapy on disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation